1995
DOI: 10.1073/pnas.92.4.1177
|View full text |Cite
|
Sign up to set email alerts
|

Induction of heme oxygenase 1 in the retina by intense visible light: suppression by the antioxidant dimethylthiourea.

Abstract: The effect of intense visible light (light damage) on the expression of heme oxygenase 1 (HO-1), a protein induced by oxidative stress, was investigated in the rat retina. A sensitive reverse transcription-PCR assay demonstrated the expression of mRNA for HO-1 as well as HO-2, the noninducible HO form, in the normal retina. As analyzed by Northern blotting, however, HO-1 mRNA was barely detectable under normal circumstances. After exposure to intense visible light, retinas had markedly higher HO-1 mRNA levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(85 citation statements)
references
References 60 publications
(40 reference statements)
5
80
0
Order By: Relevance
“…A variety of processes can cause increased intracellular production of ROS in the retina, which uniformly lead to an upregulation of HO-1 as an indicator of increased intracellular oxidant stress [28][29][30]. As one example, retinal oxidant stress with HO-1 expression is induced in rats by exposure to intense visible light and is suppressed by antioxidant treatment [31]. Evidently, chronic hyperglycaemia induces similar cellular responses in the diabetic retina, but the cause for the moderate inhibitory effect of nicanartine on experimental retinopathy remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of processes can cause increased intracellular production of ROS in the retina, which uniformly lead to an upregulation of HO-1 as an indicator of increased intracellular oxidant stress [28][29][30]. As one example, retinal oxidant stress with HO-1 expression is induced in rats by exposure to intense visible light and is suppressed by antioxidant treatment [31]. Evidently, chronic hyperglycaemia induces similar cellular responses in the diabetic retina, but the cause for the moderate inhibitory effect of nicanartine on experimental retinopathy remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Primers were synthesized by Pharmacia (Freiburg, Germany) and were designed by using the PrimerSelect software (DNAS-TAR, Madison, WI). For the analysis of HSPs the following oligonucleotides were used: ␣B-crystallin, 5Ј-TGCAGTGACAGCAGGCTTCT-3Ј and 5Ј-GAGAGCACCTGTTGGAGTCT-3Ј (Van Stipdonk et al, 2000); HSP32/ HO-1, 5Ј-AAGGAGGTGCACATCCGTGCA-3Ј and 5Ј-ATGTTGAGCAG-GAAGGCGGTC-3Ј (Kutty et al, 1995); HSP70, 5Ј-AGCTGCTGC-AGGACTTCTTC-3Ј (nt 1220 -1239) and 5Ј-GCTGATCTTGCCCTT-GAGAC-3Ј (nt 1847-1866); HSP25, 5Ј-GTTAAGACCAAGGAAG-GCGTGG-3Ј and 5Ј-CTACTTGGCTCCAGACTGTTCC-3Ј (Suzuki et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…There is great variability in the tissue distribution of the two isoforms of HO and the basal levels of HO-2 protein vary considerably from tissue to tissue. HO-2 is unaffected by light stress (Kutty et al, 1995) and is moderately expressed in normal rat retina compared with the brain and testes, which have the highest levels of HO-2 expression. It has been reported that HO-2 mRNA levels are low in human dermal fibroblasts but high in epidermal keratinocytes (Applegate et al, 1995), and it has been suggested that keratinocytes benefit from constitutively high levels of ferritin and that this is regulated by iron released as a result of the activity of the constitutive HO isozyme, HO-2.…”
Section: B Heme Oxygenase Isozymesmentioning
confidence: 97%